How Parents and Agents Can Address Bullying with Youth - Rosemary V. Barnett (EDIS)
Recently the American Medical Association (AMA) adopted a new anti-bullying policy that concluded that bullying is not just another childhood behavior that will eventually be outgrown, but rather a public health problem that can have long-term effects for both the bully and the victim. Children who don't escape the cycle of bullying are at higher risk for serious academic, social, emotional, and legal problems. This has been reinforced by a report from the AMA indicating that 7-15% of school-aged children are bullies and one in 10 school children is a victim of bullying (Peck, 2002). This document is FCS2243, one of a series of the Family, Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: December 2005.